2019
DOI: 10.3390/su11247240
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Food Sustainability Labels on the Perceived Product Value and Price Expectations of Urban Consumers

Abstract: Sustainable labelling is an important tool in raising awareness and informing potential buyers regarding environmental, economic and social issues. This study provides insights into consumers’ value of food sustainability labels through the exploration of the impact of logos on their purchasing decisions (willingness to buy (WTB)) and readiness to pay (willingness to pay (WTP)) a higher price for sustainability-labelled products. Data was collected via an online survey among a sample of 423 adult city dwellers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 50 publications
(81 reference statements)
1
47
0
2
Order By: Relevance
“…Consumers did not have explicit information about fibreenriched cake sustainability. Kaczorowska et al (2019) [42] found that sustainability labels influence consumer buying behaviour in spite of the fact that consumers perceive the benefits of buying them differently. In these ways, it should be explored whether sustainability should be a valuable reason to rise up the lower acceptability of fibreenriched cake.…”
Section: Figurementioning
confidence: 99%
“…Consumers did not have explicit information about fibreenriched cake sustainability. Kaczorowska et al (2019) [42] found that sustainability labels influence consumer buying behaviour in spite of the fact that consumers perceive the benefits of buying them differently. In these ways, it should be explored whether sustainability should be a valuable reason to rise up the lower acceptability of fibreenriched cake.…”
Section: Figurementioning
confidence: 99%
“…For the sake of simplicity, we will call it here as "sustainable labelling". In this sense, there are a huge number of organizations, promoted by groups of producers, retailers, nongovernment organizations or public authorities, that have developed their own voluntary sustainable labelling schemes to provide information to consumers about certain aspects of the food they buy or its production method [60]. In all of them, there are four common goals: (1) they provide information that consumers otherwise might not have; (2) they provide information in a format that is understandable and quickly comprehensible for most consumers; (3) its use and the verification system behind foster trust of consumers; and (4) they empower consumers.…”
Section: Impact Of Food Traders On Achieving Un Sdgs (And Vice Versa)mentioning
confidence: 99%
“…For example, Boesen et al [6] emphasized on a misperception where consumers tend to perceive SC based on the extrinsic aspect of the product such as the packaging material, not the packaging environmental impact. Such misperception tends to cause consumer misunderstandings about SC [7,26,35]. Additionally, Feil et al [36] argued that perceptions on SC are difficult to capture due to different characteristics possessed by the consumers.…”
Section: Sustainable Consumptionmentioning
confidence: 99%